Experimental study on fire temperature field of extra-long highway tunnel under the effect of auxiliary channel design parameters - Yinjun Tan; Jie Li; Huayun Li; Zhisheng Li (Case Studies in Thermal Engineering)
Accounting for the auxiliary channel's design parameters, 96 model tests on tunnel fires were conducted. The primary investigation centred on the influence of inclined shaft angle, the diameter and height of the vertical shaft on the temperature fields within extra-long highway tunnels during fires. It was observed that the HRR of a square-shaped fire source correlates linearly with the burner's surface area. The design parameters of the inclined and vertical shafts predominantly affect the temperature distribution in the vicinity of the tunnel's intersection. As the inclined shaft's angle is increased from 3° to 12°, and the vertical shaft's diameter and height are increased from 0.4 m to 0.7 m and from 4 m to 10 m, respectively, the maximum temperature variation percentages are 23.7 %, 27.3 %, and 25 %, respectively. When the angle and length of the inclined shaft are kept within 12° and 100m, changes in the shaft's angle have little impact on the temperature of the vault in front of the intersection. An increase in the vertical shaft's height from 4m to 10m results in a 14 % maximum temperature difference in the intersection's front area.